Identification of orange color-related gene, PhcpcC, in Pyropia haitanensis - Guo, Yanling; Chang, Jing; Xu, Yan; Liao, Yanqing; Ji, Dehua; Chen, Changsheng; Wang, Wenlei; Xie, Chaotian (Frontiers in Marine Science, 2024)
Pigmentation-related mutations can be utilized to distinguish between differentially colored sectors of chimeric thalli, thereby facilitating the efficient breeding of economically valuable Pyropia/Porphyra seaweed species. However, the specific trait loci and alleles responsible for Pyropia/Porphyra coloration have yet to be identified, which limits the applicability of coloration mutants for breeding and genetic analyses. In this study, to preserve the genetic integrity of the population, only four-colored thalli were considered when constructing the doubled haploid (DH) Pyropia haitanensis population, which consisted of 480 homozygous offspring lines (representing the largest DH Pyropia/Porphyra population). The offspring lines in the DH population exhibited both wild-type colored and orange sectors, with a segregation ratio of approximately 1:1, indicating that the orange coloration was controlled by a single nuclear gene. Through BSA-seq analysis (99% confidence interval), a candidate region of 0.5 Mb was identified in the P. haitanensis genome. Additionally, a non-synonymous SNP [A/G] was detected at base-pair position 481 in the coding region of PhcpcC, which encodes a phycocyanin-associated rod linker protein. This SNP locus was verified in both DH and natural populations, with the wild-type colored lines having an A base and the orange lines having a G base at this locus. Therefore, PhcpcC may be the gene associated with the orange coloration of P. haitanensis. The molecular marker developed in this study can be employed to exploit pigmentation mutants for breeding and genetic analyses of Pyropia/Porphyra species.